The Contextual Mapping of Smart City Characteristics with their Dimensions through Content Analysis Method - Vasudavan H.; Mostafa S.A.; Gunasekaran S.S.; Dhillon J.S.; Chua K.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mapping; Sustainable development; Urban growth; characteristics; Content analysis method; dimensions; Dynamic process; Smart environment; smart governance; Smart livings; Success factors; Smart city